Reduction of Peripartum Racial and Ethnic Disparities: A Conceptual Framework and Maternal Safety Consensus Bundle. (23rd April 2018) - Howell, Elizabeth A.; Brown, Haywood; Brumley, Jessica; Bryant, Allison S.; Caughey, Aaron B.; Cornell, Andria M.; Grant, Jacqueline H.; Gregory, Kimberly D.; Gullo, Susan M.; Kozhimannil, Katy B.; Mhyre, Jill M.; Toledo, Paloma; et al.
Abstract: Racial and ethnic disparities exist in both perinatal outcomes and health care quality. For example, black women are 3 to 4 times more likely to die from pregnancy‐related causes and have more than a 2‐fold greater risk of severe maternal morbidity than white women. In an effort to achieve health equity in maternal morbidity and mortality, a multidisciplinary workgroup of the National Partnership for Maternal Safety, within the Council on Patient Safety in Women's Health Care, developed a concept article for the bundle on reduction of peripartum disparities. We aimed to provide health care providers and health systems with insight into racial and ethnic disparities in maternal outcomes, the etiologies that are modifiable within a health care system, and resources that can be used to address these etiologies and achieve the desired end of safe and equitable health care for all childbearing women.